A Benchmark for Multidimensional Statistical Data - Baumgärtel, Philipp; Endler, Gregor; Lenz, Richard (Advances in Databases and Information Systems, 2013)
ProHTA (Prospective Health Technology Assessment) is a simulation project that aims at estimating the outcome of new medical innovations at an early stage. To this end, hybrid and modular simulations are employed. For this large scale simulation project, efficient management of multidimensional statistical data is important. Therefore, we propose a benchmark to evaluate query processing of this kind of data in relational and non-relational databases. We compare our benchmark with existing approaches and point out differences. This paper presents a mapping to a flexible relational model, JSON documents and RDF. The queries defined for our benchmark are mapped to SQL, SPARQL, the MongoDB query language and MapReduce. Using our benchmark, we evaluate these different systems and discuss differences between them. © 2013 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD6.abench